2017
DOI: 10.1002/2211-5463.12302
|View full text |Cite
|
Sign up to set email alerts
|

The Stl repressor from Staphylococcus aureus is an efficient inhibitor of the eukaryotic fruitfly dUTPase

Abstract: DNA metabolism and repair is vital for the maintenance of genome integrity. Specific proteinaceous inhibitors of key factors in this process have high potential for deciphering pathways of DNA metabolism and repair. The dUTP ase enzyme family is responsible for guarding against erroneous uracil incorporation into DNA . Here, we investigate whether the staphylococcal Stl repressor may interact with not only bacterial but also eukary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Remarkably, the catalytic activity of Φ11 dUTPase (Φ11DUT) is also inhibited upon complex formation with Stl, due to the competition of Stl and the substrate dUTP for dUTPase binding revealed by transient kinetic analysis 42 . Moreover, in our recent studies we have also demonstrated that Stl acts as a potent inhibitor of the Mycobacterial dUTPase, both in vitro and in vivo 21 and exerts inhibitory effect on the Drosophila melanoglaster dUTPase in vitro 43 .…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Remarkably, the catalytic activity of Φ11 dUTPase (Φ11DUT) is also inhibited upon complex formation with Stl, due to the competition of Stl and the substrate dUTP for dUTPase binding revealed by transient kinetic analysis 42 . Moreover, in our recent studies we have also demonstrated that Stl acts as a potent inhibitor of the Mycobacterial dUTPase, both in vitro and in vivo 21 and exerts inhibitory effect on the Drosophila melanoglaster dUTPase in vitro 43 .…”
Section: Introductionmentioning
confidence: 78%
“…aureus Φ 11 and 80 α phages, M . tuberculosis , and D. melanogaster in vitro 21 , 42 , 43 , although the latter two proteins share only modest sequence similarity with the original phage dUTPase partners of Stl. Using various techniques we have now demonstrated that Stl also interacts with the human dUTPase, which displays 62% sequence similarity to the phage dUTPases (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different strains of S. aureus encode numerous mutated versions of SAUGI [18]. While the exact biological role of SAUGI is still unclear, it is highly interesting to note that S. aureus also encodes an inhibitory protein for dUT-Pase, namely Stl [23][24][25][26][27].…”
mentioning
confidence: 99%